Pedagogical Competence and Achievement Motivation as Predictors of Teacher Performance : The Mediating Role of Organizational Commitment (International Journal of Economics and Management Research, 2025)
The purpose of this study is to analyze the mediating role of organizational commitment in the relationship between pedagogical competence and achievement motivation on teacher performance, with the primary goal of enhancing overall teacher performance. The research population consists of 737 teachers who are members of the Madrasah Working Group (KKM) in the Semarang region, and the sample of 180 respondents was selected using proportional random sampling. This study employs a quantitative descriptive method, and data were collected through questionnaires distributed to all participating teachers. Data analysis was conducted using PLS-SEM with the SmartPLS 3 application. The hypothesis testing results indicate that pedagogical competence, achievement motivation, and organizational commitment have a positive and significant effect on teacher performance. Furthermore, pedagogical competence and achievement motivation also show a positive and significant effect on organizational commitment. Mediation testing using the Sobel method reveals that organizational commitment successfully mediates the effects of both pedagogical competence and achievement motivation on teacher performance.